dc Josephson current for d-wave superconductors with charge density waves - Gabovich, A.M.; Voitenko, A.I. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2012)
dc Josephson tunnel current Ic between a dx2–y2-wave superconductor with charge density waves (CDWs) — e.g., a high-Tc oxide and a conventional isotropic superconductor — was considered theoretically. A directionality of tunneling was taken into account. It was found that the dependence of Ic on the angle γ between the superconductinglobe direction and the normal to the junction plane is significantly altered by CDWs. For certain doping levels it may be even nonmonotonic, which can be readily found experimentally. For the sake of comparison, the corresponding results obtained for the tunnel junction between a CDW s-superconductor and a conventionalisotropic superconductor are also presented.